Liquid chromatography-drift tube ion mobility-mass spectrometry as a new challenging tool for the separation and characterization of silymarin flavonolignans - Fenclova, Marie; Stranska-Zachariasova, Milena; Benes, Frantisek; Novakova, Alena; Jonatova, Petra; Kren, Vladimir; Vitek, Libor; Hajslova, Jana (Analytical and bioanalytical chemistry, 2020)
Silymarin, milk thistle (Silybum marianum) extract, contains a mixture of mostly isomeric bioactive flavonoids and flavonolignans that are extensively studied, especially for their possible liver-protective and anticancer effects. Because of the differing bioactivities of individual isomeric compounds, characterization of their proportion in a mixture is highly important for predicting its effect on health. However, because of silymarin's complexity, this is hardly feasible by common analytical techniques. In this work, ultraperformance liquid chromatography coupled with drift tube ion mobility spectrometry and quadrupole time-of-flight mass spectrometry was used. Eleven target silymarin compounds (taxifolin, isosilychristin, silychristins A and B, silydianin, silybins A and B, 2,3-cis-silybin B, isosilybins A and B and 2,3-dehydrosilybin) and five unknown flavonolignan isomers detected in the milk thistle extract were fully separated in a 14.5-min analysis run. All the compounds were characterized on the basis of their accurate mass, retention time, drift time, collision cross section and fragmentation spectra. The quantitative approach based on evaluation of the ion mobility data demonstrated lower detection limits, an extended linear range and total separation of interferences from the compounds of interest compared with the traditional approach based on evaluation of liquid chromatography-quadrupole time-of-flight mass spectrometry data. The following analysis of a batch of milk thistle-based food supplements revealed significant variability in the silymarin pattern, especially in the content of silychristin A and silybins A and B. This newly developed method might have high application potential, especially for the characterization of materials intended for bioactivity studies in which information on the exact silymarin composition plays a crucial role. Graphical Abstract.
Keywords: silymarin; ostropestřec mariánský; Silybum marianum; Milk thistle; Flavonolignans; Isomerism; Ultraperformance liquid chromatography; Mass Spectrometry; isomerie; Ion Mobility Spectrometry; iontová mobilní spektrometrie; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; Silymarin; Collision cross section; Drift tube ion mobility high-resolution mass spectrometry; hmotnostní spektrometrie; flavonolignany